Modelling and control of semi active suspension system incorporating magnetorheological damper for generic vehicle - Sulaiman, Syabillah (2017)
This study presents the simulation and experimental works for Magnetorheological (MR) semi active suspension system in generic vehicles. In simulation study, a seven degree of freedom (7-DOF) vehicle model was developed using MATLAB-Simulink and verified using TruckSim. A semi active controller with road friendliness oriented was developed to reduce vehicle tire force; besides, ride comfort becomes the secondary objective of the proposed controller. The proposed semi active controllers which are Tire Force Control (TFC), Aided Tire Force Control (ATFC) and ground Semi Active Damping Force Estimator (gSADE) and simulation results were compared with existing controller known as Groundhook (GRD) and passive suspension system. Then, these controllers were applied experimentally using generic quarter vehicle model. The overall results showed gSADE is the most effective controller in reducing vehicle tire force and improving ride comfort. Both reduction of gSADE vehicle tire force and ride comfort compared with passive system are similar about 14.2%. In the simulation study, ideal and real cases (using MR damper model) were conducted. In the ideal case, two bump profiles were used to test the effectiveness of the controller and the results showed gSADE recorded the highest improvement of the tire force followed by ATFC, TFC, GRD and passive system. The maximum improvement of gSADE control compared with passive system is about 21% in reduction of tire force and 22% in improving ride comfort. A similar test was conducted using MR damper model, and the overall result showed gSADE recorded almost similar improvement of the tire force compared with TFC. The maximum reduction of vehicle tire force and improvement of ride comfort using gSADE control compared with passive are 15% and 30%, respectively.